Coral Cover and Diversity Life form in Different Reef Zone at Kampung Baru Waters, Bintan Island: Tutupan dan Keanekaragaman (Life form) Karang Pada Zona Terumbu Berbeda di Perairan Kampung Baru Bintan - Anna Kristine Sigarlaki; Aditya Hikmat Nugraha; Dedy Kurniawan (Tropical Fisheries Management Journal, 2021)
The purpose of this study was to compare the percentage of cover conditions, diversity index, uniformited index and dominance index of life form coralin the zones reef flate and reef slope in Kampung Baru Lagoi, Bintan Regency. This research was conducted using the method Line Intersept Transect (LIT) with the line transect length used was 30 meters, three replications with a gap of 5 meters. The results showed, at point station 1 in the zone flate Reef the percentage of live coral cover was 36,92% are categorized as moderate. Forms the coral growth Life form were found as many 9 types of Life form hard corals namely ACB, ACT, ACE, ACS, ACD, CB, CM, CE, CS with a diversity index of 2,53 are categorized as moderate, a uniformited index of 0,80 are categorized as high, and a dominance index of 0,22 are categorized as low. At the point station 2 in the zone slope Reef the percentage of live coral cover was 50,44% are categorized as good. Forms of coral growth (Life form) were found as many as 8 types of Life form hard corals namely ACT, ACE, CB, CM, CE, CS, CF and CMR, with a diversity index of 2,13 are categorized as moderate, a uniformited index of 0,71 are categorized as high, and a dominance index of 0,30 are categorized as low.